Sarcoidosis Phenotyping: Analysis of Current Approaches (Review) - A. A. Vizel; S. N. Avdeev; I. Yu. Vizel; G. R. Shakirova (Туберкулез и болезни лёгких)
The review analyzes publications devoted to the formation of phenotypes in sarcoidosis patients. It has been noted that there is a certain difficulty in phenotyping the disease that can affect all human organs and systems. The article demonstrates the trend to shift from Scadding radiographic stages of intrathoracic sarcoidosis, based on radiography, to phenotypes based on high-resolution computed tomography. It presents phenotypes based on such parameters as organ damage, respiratory dysfunction, laboratory and genetic data, and treatment effects. The authors note that phenotypes should be applicable to clinical practice and clearly reflect differences between patients and the likelihood of clinically significant outcomes.